Mutation analysis of 21 autosomal short tandem repeats in Han population from Hunan, China - Wei Xu; Yuequn Wang; Dandan Zhang; Daixin Wang; Liang Zhou; Xiangli Ye; Chaogeng Zhu; Yongzhong Shi (Taylor & Francis Group, 2019)
Background: Short tandem repeats (STRs) are powerful genetic markers widely used in human genetics. Population data and locus-specific mutation rates of STRs are crucial for the evaluation and interpretation of genetic evidence in forensic and population genetics. Aim: To investigate the mutation rates of 21 autosomal STRs in a population from central south China. Subjects and methods: This study analysed 3420 paternity cases with a Combined Paternity Index >10,000 from Han population in Hunan. A total of 68,743 meiotic transfers were analysed and 62 mutations were identified. Results: The overall mutation rate of STR loci was 0.9 × 10−3 (95% CI, 0.0007-0.0011) and the locus-specific mutation rates were estimated ranging from 0.0000-0.0023. Locus D1S1656 exhibited the highest mutation rate of 2.3 × 10−3 (95% CI, 0.0005-0.0006), followed by D12S391 with a mutation rate of 2.0 × 10−3 (95% CI, 0.0007-0.0044). No mutation was observed at TPOX, D2S1338 or Penta D. One-step mutation cases accounted for 96.77% of total mutations and the ratio of paternal vs maternal mutations was ∼4.85:1. Inter-population comparisons of locus-specific mutation rates of several STRs revealed significant differences between Han in Hunan and Han in other regions of China. Conclusion: The data justified the use of geographical data in further genetic applications.